Characteristic properties of laser ablation of translucent targets. (31st May 2018) - Platonov, V V; Kochurin, E A; Osipov, V V; Lisenkov, V V; Zubarev, N M
Abstract: This study reveals the characteristic features of the laser ablation of the solid Nd:Y2 O3 targets, such as the dynamics of the laser plume, the crater depth, and the weight and size distribution of liquid melt droplets. The ablation was initiated by the ytterbium fiber laser radiation pulses with constant energy (0.67 J) and with different power densities. The dependence on the power density of such parameters as the injection time of drops, mass distribution of drops, crater depth, and productivity of synthesis of nonopowder was revealed. To explain the formation of deep craters a model was proposed, stating that the formation of liquid droplets is a consequence of the Kelvin–Helmholtz instability's appearing and developing on the border between the liquid melt on the crater's wall and the vapor flow from the crater. The increment of this instability and its characteristic size was determined.